If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 7 = 3x + 9 Reorder the terms: 7 + 5x = 3x + 9 Reorder the terms: 7 + 5x = 9 + 3x Solving 7 + 5x = 9 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 7 + 5x + -3x = 9 + 3x + -3x Combine like terms: 5x + -3x = 2x 7 + 2x = 9 + 3x + -3x Combine like terms: 3x + -3x = 0 7 + 2x = 9 + 0 7 + 2x = 9 Add '-7' to each side of the equation. 7 + -7 + 2x = 9 + -7 Combine like terms: 7 + -7 = 0 0 + 2x = 9 + -7 2x = 9 + -7 Combine like terms: 9 + -7 = 2 2x = 2 Divide each side by '2'. x = 1 Simplifying x = 1
| 3-3y=9-4y | | (x+7)=(24+26) | | y-1=3(x+6) | | y-5=3(x-1) | | 67-4x=5x+18 | | 8x+v=3x+w | | 8-9x=89-30x | | Y=mx+bx | | y+2=-6(x+6) | | T=3+1.25(13) | | 6x+36=15x-54 | | 6x-5=-3 | | 8y-2=13y+33 | | 5(5x-4)-4(3x-6)= | | -46-2x=8-8x | | -4-6n=7n+3 | | 2x-6x=4x+3 | | T=3+1.25c | | -4n-6=7n+3 | | 3(4x+1)+2(6x-9)= | | 5h-3h+9h=176 | | 12500=.5x^2+11x+4000 | | -4m=28 | | 48=7t-3t | | 7(x+7)+5(2x-8)= | | 2y+5+4y=6y+3 | | -3+7=-10 | | 2x^2=450 | | y+4y=95 | | (2x-1)(3x+5)=0 | | -36=j+13 | | 8f+4e=16 |